2017
DOI: 10.1038/ncomms14861
|View full text |Cite
|
Sign up to set email alerts
|

The conserved protein Seb1 drives transcription termination by binding RNA polymerase II and nascent RNA

Abstract: Termination of RNA polymerase II (Pol II) transcription is an important step in the transcription cycle, which involves the dislodgement of polymerase from DNA, leading to release of a functional transcript. Recent studies have identified the key players required for this process and showed that a common feature of these proteins is a conserved domain that interacts with the phosphorylated C-terminus of Pol II (CTD-interacting domain, CID). However, the mechanism by which transcription termination is achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
74
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 72 publications
7
74
0
Order By: Relevance
“…The NIM is one of the very few sequence regions of the C-terminal domain of Sen1 that are 3 conserved in the closest S. cerevisiae relatives, suggesting that this mode of interaction 4 between Sen1 and Nrd1 is conserved in these yeast species (figure EV1). Conversely, in 5 agreement with previous data showing that Nrd1 and Sen1 orthologues do not interact with 6 each other in S. pombe (Lemay et al, 2016;Wittmann et al, 2017) and with the fact that no 7 Nrd1 homologue could be identified in association with human Sen1(Yüce and West, 2013), 8 we did not detect any putative NIM in Sen1 orthologues from these organisms. 9 10 Structural analyses of the Nrd1 CID-Sen1 NIM interaction 11 To compare the interaction of the newly identified Sen1 NIM (fragment harboring amino acids 12 2052-2063) and the previously identified Trf4 NIM with Nrd1 CID, we performed a quantitative 13 solution-binding assay using fluorescence anisotropy (FA) with purified recombinant Nrd1 CID 14 and synthetic NIM peptides.…”
supporting
confidence: 90%
“…The NIM is one of the very few sequence regions of the C-terminal domain of Sen1 that are 3 conserved in the closest S. cerevisiae relatives, suggesting that this mode of interaction 4 between Sen1 and Nrd1 is conserved in these yeast species (figure EV1). Conversely, in 5 agreement with previous data showing that Nrd1 and Sen1 orthologues do not interact with 6 each other in S. pombe (Lemay et al, 2016;Wittmann et al, 2017) and with the fact that no 7 Nrd1 homologue could be identified in association with human Sen1(Yüce and West, 2013), 8 we did not detect any putative NIM in Sen1 orthologues from these organisms. 9 10 Structural analyses of the Nrd1 CID-Sen1 NIM interaction 11 To compare the interaction of the newly identified Sen1 NIM (fragment harboring amino acids 12 2052-2063) and the previously identified Trf4 NIM with Nrd1 CID, we performed a quantitative 13 solution-binding assay using fluorescence anisotropy (FA) with purified recombinant Nrd1 CID 14 and synthetic NIM peptides.…”
supporting
confidence: 90%
“…Our inspection of the structure of S. pombe Seb1 (43) suggests that it may have a counterpart of the lysine-rich surface motif responsible for inositol polyphosphate binding in the ENTH domain (40). Seb1 interacts physically with the fission yeast CPF complex (43). It is conceivable that IPP interaction with Seb1 (or one of the other fission yeast CID proteins) enhances 3'-processing/termination.…”
Section: Discussionmentioning
confidence: 99%
“…The NIM is one of the very few sequence regions of the C-terminal domain of Sen1 that are conserved in the closest S. cerevisiae relatives, suggesting that this mode of interaction between Sen1 and Nrd1 is conserved in these yeast species ( Fig EV1) pombe (Lemay et al, 2016;Wittmann et al, 2017) and with the fact that no Nrd1 homologue could be identified in association with human Sen1(Yü ce & West, 2013), we did not detect any putative NIM in Sen1 orthologues from these organisms.…”
Section: Sen1 Possesses a Ctd Mimic That Is Recognized By The Cid Dommentioning
confidence: 99%